2014
DOI: 10.1364/oe.22.012836
|View full text |Cite
|
Sign up to set email alerts
|

Generation of quasi-monoenergetic electron beams with small normalized divergences angle from a 2 TW laser facility

Abstract: We report the generation of a 6 pC, 23 MeV electron bunch with the energy spread ± 3.5% by using 2 TW, 80 fs high contrast laser pulses interacting with helium gas targets. Within the optimized experimental condition, we obtained quasi-monoenergetic electron beam with an ultra-small normalized divergence angle of 92 mrad, which is at least 5 times smaller than the previous LPA-produced bunches. We suggest the significant decrease of the normalized divergence angles is due to smooth transfer from SM-LWFA to LWF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…One regime was obtained for the laser pulse duration of ∼200 fs, and plasma density in the range of 3.6-4×10 19 -1.1×10 20 cm −3 , as described above. Another regime of electron acceleration was observed at the comparatively lower laser pulse duration of ∼55 fs, where the generation of QM electron beams of peak energy ∼30 MeV with almost 100% reproducibility (similar to our earlier observation [23] and various other reports [16][17][18][19][20][21][22][23]) was observed, and this could be attributed to the SM-LWFA mechanism. Figure 6 shows a typical QM electron beam spectrum recorded at the laser pulse duration of ∼55 fs during the same experimental run.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One regime was obtained for the laser pulse duration of ∼200 fs, and plasma density in the range of 3.6-4×10 19 -1.1×10 20 cm −3 , as described above. Another regime of electron acceleration was observed at the comparatively lower laser pulse duration of ∼55 fs, where the generation of QM electron beams of peak energy ∼30 MeV with almost 100% reproducibility (similar to our earlier observation [23] and various other reports [16][17][18][19][20][21][22][23]) was observed, and this could be attributed to the SM-LWFA mechanism. Figure 6 shows a typical QM electron beam spectrum recorded at the laser pulse duration of ∼55 fs during the same experimental run.…”
Section: Discussionsupporting
confidence: 90%
“…A laser pulse of short duration, such that L=cτλ p is used, where L is laser pulse length, c is speed of light, τ is FWHM (full width at half maximum) pulse duration, and λ p is plasma wavelength. However, the generation of QM electron beams of a few tens of MeV energies have also been demonstrated by the self-modulated laser wakefield acceleration (SM-LWFA) [16][17][18][19][20][21][22][23] regime at comparatively higher plasma densities (L?λ p ) , by using laser pulses as long as 90 fs, and it was suggested that small laser pulselets that formed due to the self-modulation of the laser pulse could create bubble regime conditions [16]. Earlier reported experiments with comparatively longer laser pulses (a few hundreds of fs to ps) also generated relativistic electron beams through SM-LWFA but with a broad continuous spectrum [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For 118 (30) TW pulses, the focused peak intensity and the corresponding normalized vector potential a 0 were 8.7 × 10 18 (2.6 × 10 18 ) W/cm 2 and 2.1 (1.1), respectively. The density of the laser-produced plasma from both nozzles (4 mm and 1 cm) was probed by interferometery and forward Raman scattering (FRS) diagnostics in previous experiments and comparted with hydrodynamic calculations of the gas density 38 39 40 . The nozzle was positioned below the laser spot at a vertical height of 2 mm and the gas valve was triggered 4.5 ms (which is the time it takes for the gas density to reach maximum at nozzle exit) before arrival of the laser pulse.…”
Section: Methodsmentioning
confidence: 99%